2020
DOI: 10.1108/mrr-03-2020-0130
|View full text |Cite
|
Sign up to set email alerts
|

Workplace cyberbullying and creativity: examining the roles of psychological distress and psychological capital

Abstract: Purpose This study aims to investigate the effects of workplace cyberbullying on creativity directly and through psychological distress. Furthermore, this study proposes that psychological capital (PsyCap) buffers the harmful effects of workplace cyberbullying on psychological distress and creativity. Design/methodology/approach The data were collected in two waves from 329 nurses working in four large public hospitals located in a metropolitan city of Pakistan. The data were analyzed through PROCESS (Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 85 publications
(67 reference statements)
0
29
0
6
Order By: Relevance
“…In total, 60 articles were examined to investigate the impacts of speaking with a non-native English accent, which were categorized into three aspects: (i) affective impact [ 16 , 17 , 18 , 19 , 20 ]; (ii) behavioral impact [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; and (iii) cognitive impact [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 60 articles were examined to investigate the impacts of speaking with a non-native English accent, which were categorized into three aspects: (i) affective impact [ 16 , 17 , 18 , 19 , 20 ]; (ii) behavioral impact [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; and (iii) cognitive impact [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71…”
Section: Resultsmentioning
confidence: 99%
“…Attitudes may impact the perception of the comprehensibility of the speakers. The different variations of English are cherished as ESL/EFL called for a more active recognition and encouraging measures to increase awareness of the global expansion of English throughout the world, which has conceived many localized versions of the language [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hazards of harassment via ICT and social media, in particular, could take numerous forms, including drawings, words, photos, animations, and videos, with the material intended to humiliate or hurt the recipient directly or indirectly (Kowalski and Robbins, 2021). Similarly, Kalyar et al (2020) contends that cyberbullying hazards can manifest themselves in a variety of formats, including text, drawing, photos, animations, and videos, in which the information undermines, humiliates, or injures the individual directly or indirectly. According to Zhang (2021), the risk of workplace bullying is four times greater than the risk of workplace discrimination.…”
Section: The Risks Of Cyber Bullying In the Workplacementioning
confidence: 99%
“…Because companies have a legal obligation to provide a safe working environment for their employees (Farley, 2021), they risk being held vicariously liable for any bullying that occurs in the workplace, particularly bullying committed by an employee against another employee (Kalyar et al, 2020). Hsieh et al (2019) rightly propose that businesses implement anti-bullying and anti-discrimination policies that enable effective complaint and grievance channels of communication and processes especially when the majority of workers are online.…”
Section: Managing the Risks Of Cyber Bullying At Workmentioning
confidence: 99%
“…As Oshio, Inoue, & Tsutsumi (2017) stated, work-family conflicts happen when individuals simultaneously face the demands of work and have to undergo various roles and obligations related to family life Psychological distress refers to the emotional suffering experienced by individuals due to difficulties coping with stressors and demands in daily life (Islam, 2019). Research showed psychological distress had been linked to increased mortality due to various health problems such as cardiovascular problems, chronic obstructive pulmonary problems, and cancer (McLachlan & Gale, 2018;Russ et al, 2012) and can reduce employee creativity (Kalyar, Saeed, Usta, & Shafique, 2021). Psychological distress is caused by conflicts that arise between the role of work and family and affects spousal Work from home is one of the policies chosen by the government due to the COVID -19 pandemic; however, work-home interactions (WHIs) can place a burden on one domain.…”
Section: Introductionmentioning
confidence: 99%